Method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate lithium extraction slag and application of battery-grade lithium iron manganese phosphate

Through acid leaching, co-precipitation and hydrothermal reaction, battery-grade lithium manganese phosphate is directly prepared from waste lithium iron phosphate batteries, solving the problems of resource waste and high cost, and achieving high efficiency and high purity lithium manganese phosphate Recycling and reuse.

CN119263249APending Publication Date: 2025-01-07湖北金泉新材料有限公司

Patent Information

Application Number
CN202411681333.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and reuse lithium manganese phosphate materials in waste lithium iron phosphate batteries, resulting in waste of resources and high costs.

Method used

Through acid leaching, co-precipitation reaction, hydrothermal reaction and sintering processes, battery-grade lithium manganese phosphate materials are directly prepared from phosphate slag, avoiding additional manganese element doping and lithium matching processes, and improving recovery and material purity.

Benefits of technology

The recovery rate of more than 96% of phosphorus and iron in waste slag is achieved. The obtained lithium manganese iron phosphate material has high purity, small particle size and uniform distribution, and the electrical performance reaches the battery level standard, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263249A_ABST
    Figure CN119263249A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate lithium extraction slag and application of the battery-grade lithium iron manganese phosphate. The preparation method comprises the following steps: carrying out acid leaching on the ferrophosphorus slag to obtain a leaching solution and leaching slag; adding a manganese salt and an iron salt into the leachate to supplement manganese and iron, and then mixing with a precipitant solution and a complexing agent solution to carry out coprecipitation reaction to obtain a ferromanganese phosphate precursor; carrying out hydrothermal reaction on the ferromanganese phosphate precursor and a lithium source to obtain a lithium ferromanganese phosphate precursor; and sintering the lithium manganese iron phosphate precursor to obtain the battery grade lithium manganese iron phosphate, wherein acid adopted in the acid leaching process comprises phosphoric acid. According to the preparation method provided by the invention, the recovery rate of phosphorus and iron in the waste residues can reach 96% or above, the obtained lithium manganese iron phosphate material is high in purity, small in particle size and uniform in distribution, and the electrical property can reach the level of battery-grade lithium manganese iron phosphate; in addition, the preparation method is short in technological process, high in production efficiency and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery material recovery, and relates to a method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag and its application. Background Art

[0002] Lithium iron phosphate batteries are widely used in the field of new energy vehicles due to their low price, good safety, stable chemical properties and excellent cycle performance. Their market share in the new energy vehicle market has exceeded 70%, and is showing a trend of continuous growth worldwide. The service life of new energy vehicles is about 5 to 8 years, which means that a large number of waste lithium iron phosphate batteries are generated every year. These huge waste battery materials contain rich lithium, iron and phosphorus elements, which are important secondary energy sources. Therefore, if waste lithium iron phosphate batteries can be recycled and reused, it can not only realize the recycling of battery materials, but also protect the environment, and has broad development prospects.

[0003] CN115893349A discloses a process for recovering iron phosphate from iron phosphate slag by a wet phosphoric acid process. The process comprises adding a surfactant, calcium hydroxide and glucose to the iron phosphate slag, reducing and roasting the slag at high temperature, and then performing magnetic separation to obtain iron powder and calcium phosphate. The calcium phosphate is dissolved by concentrated sulfuric acid to obtain calcium sulfate and dilute phosphoric acid. The dilute phosphoric acid is purified and concentrated, and then reacted with the iron powder. The slag is then dehydrated and demagnetized at high temperature to obtain recovered iron phosphate.

[0004] CN116281916A discloses a method for wet recycling of waste lithium iron phosphate positive electrode materials, which includes: separating waste lithium iron phosphate batteries to obtain lithium-containing positive electrode material powder; soaking the lithium-containing positive electrode material powder in an organic solvent; pressing the lithium positive electrode material powder and a binder into blocks and calcining them to obtain a mixture; subjecting the mixture and a reducing agent to high-temperature vacuum reduction, vacuum distillation and vacuum condensation in sequence to obtain metallic lithium and residue; dissolving the residue in an inorganic acid solution and adding a precipitant, and drying the precipitate; heating the dried precipitate and cooling it to room temperature to obtain iron phosphate.

[0005] However, although the above recycling process can recover iron phosphate from waste lithium iron phosphate batteries, the process is relatively complicated. Moreover, the economic value of the iron phosphate produced is low and it cannot be directly used as the positive electrode material of lithium-ion batteries. It still needs additional lithium addition and sintering processes, which increases the cost of recycling. In view of this, most recycling companies still export ferrophosphorus slag to phosphorus chemical companies at low prices, or even treat it as solid waste, causing economic losses and a large waste of phosphorus and iron resources.

[0006] Lithium iron manganese phosphate is considered to be an upgraded version of lithium iron phosphate. It has similar properties to lithium iron phosphate and lithium manganese phosphate. It has better thermal stability, chemical stability and economy than ternary materials, and has higher energy density than lithium iron phosphate. Therefore, it has received great attention. Therefore, how to prepare lithium iron manganese phosphate materials with battery-grade standards from waste lithium iron phosphate battery materials, effectively reduce costs, and achieve large-scale mass production is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method and application of preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag. The preparation method provided by the present invention can make the recovery rate of phosphorus and iron in the waste slag reach more than 96%, and the obtained lithium iron manganese phosphate material has high purity, small particle size and uniform distribution, and the electrical performance can reach the level of battery-grade lithium iron manganese phosphate; and the preparation method of the present invention has a short process flow, high production efficiency, and is suitable for large-scale production.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing battery-grade lithium iron manganese phosphate by extracting lithium iron phosphate slag, the method comprising the following steps:

[0010] The ferrophosphorus slag is subjected to acid leaching to obtain a leaching solution and a leaching slag;

[0011] Adding manganese salt and iron salt to the leaching solution to supplement manganese and iron, and then mixing with a precipitant solution and a complexing agent solution to perform a coprecipitation reaction to obtain a manganese iron phosphate precursor;

[0012] The manganese iron phosphate precursor is subjected to a hydrothermal reaction with a lithium source to obtain a manganese iron phosphate lithium precursor;

[0013] Sintering the lithium iron manganese phosphate precursor to obtain the battery-grade lithium iron manganese phosphate;

[0014] Wherein, the acid used in the acid leaching process includes phosphoric acid.

[0015] The preparation method provided by the present invention directly prepares the lithium iron phosphate material through the coordinated cooperation of acid leaching, coprecipitation reaction, solvent thermal reaction and sintering process. Compared with the traditional process that can only obtain iron phosphate material, the lithium iron phosphate material obtained by the present invention can be directly used as a positive electrode material for the battery, without the need to perform additional manganese doping, lithium matching and sintering processes on the iron phosphate material, making the recycling of the entire waste lithium iron phosphate battery more efficient and more valuable. The preparation process of the present invention can make the recovery rate of phosphorus and iron in the waste residue reach more than 96%, and the obtained lithium iron phosphate material has high purity, small particle size and uniform distribution, and the electrical performance can reach the level of battery-grade lithium iron phosphate; and the preparation method of the present invention has a short process flow, high production efficiency, and is suitable for large-scale production.

[0016] The present invention uses phosphoric acid in the acid leaching process and adds manganese salt and iron salt to the leachate to supplement manganese and iron, which can play two roles: on the one hand, the use of phosphoric acid can avoid the introduction of additional impurity elements, and the supplementation of manganese and iron in the leachate can increase their concentration in the leachate, thereby promoting the precipitation process of manganese and iron elements, and the two cooperate with each other to jointly improve the purity of the product. On the other hand, adding manganese salt and iron salt to the leachate can adjust the ratio of manganese and iron elements in the obtained lithium manganese iron phosphate product, thereby achieving the control of the ratio of manganese and iron elements in the product.

[0017] In addition, the present invention prepares the lithium iron manganese phosphate precursor step by step through coprecipitation reaction and solvent thermal reaction. On the one hand, ferromanganese phosphate is first prepared through coprecipitation reaction, so that the product can be purer. At the same time, hydrothermal reaction is carried out with lithium hydroxide on the basis of ferromanganese phosphate, so that the filtrate is mainly lithium hydroxide, thereby realizing the recycling of lithium hydroxide solution; on the other hand, the coprecipitation reaction and the hydrothermal reaction cooperate with each other to jointly control the particle size of the precursor, so that the product particle size is small and uniform.

[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0019] Preferably, during the acid leaching process, the liquid-to-solid ratio is (2-5):1, for example 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the concentration of the phosphoric acid is 60% to 80%, such as 60%, 65%, 70%, 75% or 80%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] Preferably, the acid leaching temperature is 50-90°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the acid leaching time is 1 to 5 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the amount of phosphoric acid added is 1.0 to 1.5 times the theoretical mass of acid-hydrolyzed lithium iron phosphate, such as 1.0 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times or 1.5 times, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In the present invention, the leaching rate of phosphorus and iron can be further improved by regulating the amount of phosphoric acid added. If the amount added is too low, part of phosphorus and iron in the ferrophosphorus slag will not be fully leached, the leaching rate is low, and the purity of the ferrophosphorus slag is low.

[0025] Preferably, the pH of the leachate is 0.5 to 1.2, such as 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 or 1.2, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0026] It should be noted that the leached residue product after acid leaching in the present invention is solid carbon powder.

[0027] Optionally, the carbon powder is washed.

[0028] Optionally, the washing comprises: adding carbon powder to pure water, stirring and slurrying, and passing through a filter press until the filtrate is neutral.

[0029] Optionally, the filtrate from washing the carbon powder is reused as acid leaching slurry water, and the filter cake is directly sold out after drying.

[0030] The present invention can obtain high-purity solid carbon powder by using phosphoric acid for acid leaching. After simple washing treatment, the washing filtrate can be reused, so that the recovery rate of the carbon powder reaches 100%, which not only solves the secondary pollution generated by waste residues, but also realizes the reuse of carbon powder.

[0031] Preferably, the pH of the coprecipitation reaction is 3.5-7, preferably 3.5-5.0, for example 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5 or 7.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In the present invention, by regulating the pH of the coprecipitation reaction, the purity of the ferromanganese phosphate precursor can be further improved, and the ratio of iron and manganese elements in the product can be within a reasonable range. If the pH is high, other impurities may be generated and wrapped around each other. For example, divalent manganese is easily oxidized to hydroxyl manganese oxide, so impurities such as iron hydroxide and hydroxyl manganese oxide may appear, resulting in a decrease in product purity; if the pH is low, the precipitation of iron and manganese elements will be incomplete, resulting in low precipitation efficiency and an imbalance in the ratio of iron and manganese elements in the product.

[0033] Preferably, the reaction temperature of the coprecipitation reaction is 30-90°C, for example 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In the present invention, by regulating the temperature of the coprecipitation reaction, the purity of the product can be further improved, and the control of the product particle size distribution can be better achieved. If the coprecipitation temperature is too low or too high, it is not conducive to the coprecipitation process of iron ions and manganese ions, and is not conducive to the preparation of products with smaller particle sizes and uniform distribution. If the temperature is too low, the activity of the reaction is low and the precipitation efficiency is low, and the impurity ions will also be adsorbed on the surface of the product or wrapped in the product due to low solubility, resulting in a decrease in product purity; if the temperature is too high, from a kinetic point of view, the reaction is rapidly nucleated due to high activity, and the nucleation rate is greater than the growth rate, resulting in small primary particles in the product and serious agglomeration.

[0035] Preferably, the reaction time of the coprecipitation reaction is 1 to 5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In the present invention, by regulating the duration of the coprecipitation reaction, the purity of the product can be further improved, and it is helpful to obtain a product with a smaller particle size and a more uniform distribution. If the coprecipitation reaction time is too short, the precipitation will be incomplete, reducing the recovery rate of iron; if the time is too long, other impurity ions will be wrapped in the grains, causing the product purity to decrease, and a long reaction time will also increase the product particle size.

[0037] Preferably, the product after the coprecipitation reaction is washed and dried in sequence.

[0038] Preferably, the precipitant includes any one of sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia water, ammonium carbonate, and ammonium bicarbonate, or a combination of at least two thereof.

[0039] Preferably, the complexing agent comprises any one of ammonia, citric acid, oxalic acid and a hydroxycarboxylate complexing agent or a combination of at least two thereof.

[0040] Preferably, the ratio of the sum of the total molar amounts of manganese and iron in the manganese ferrophosphate precursor to the molar amount of lithium in the lithium source is 1:(2-3), for example, 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8 or 1:3, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Optionally, the manganese source includes any one or a combination of at least two of soluble divalent manganese salts such as manganese sulfate, manganese nitrate, and manganese chloride.

[0042] Optionally, the iron source includes any one or a combination of at least two of soluble iron salts such as ferric sulfate, ferrous sulfate, ferric nitrate, ferrous nitrate, ferric chloride, and ferrous chloride.

[0043] Optionally, when the iron source is a divalent iron source, it is used in combination with an oxidant hydrogen peroxide.

[0044] Preferably, the concentration of the lithium source solution is 0.5-1.3 mol / L, such as 0.5 mol / L, 0.7 mol / L, 0.9 mol / L, 1.1 mol / L or 1.3 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the lithium source comprises lithium hydroxide.

[0046] In the present invention, lithium hydroxide is selected as the lithium source, and no additional OH is required during the hydrothermal reaction. - , which can simplify the preparation process.

[0047] Preferably, the molar ratio of the lithium source to the ferromanganese phosphate is (2-3):1, for example 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the reaction temperature of the hydrothermal reaction is 150-250°C, for example 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In the present invention, by regulating the reaction temperature of the hydrothermal reaction, the morphology and structure of the product can be better controlled. If the reaction temperature is too high, the particles will be too fine and the compaction density will be too small; if the reaction temperature is too low, the reaction will be insufficient and the crystallization effect will be poor.

[0050] Preferably, the reaction time of the hydrothermal reaction is ≥ 2 h, for example 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] Preferably, the stirring rate of the hydrothermal reaction is 100-250 r / min, for example 100 r / min, 120 r / min, 140 r / min, 160 r / min, 180 r / min, 200 r / min, 220 r / min or 250 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the reaction pressure of the hydrothermal reaction is 1.2-1.8 MPa, for example, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa or 1.8 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] Preferably, the lithium manganese iron phosphate precursor is first mixed with a carbon source and then sintered.

[0054] Preferably, said mixing comprises solid phase mixing.

[0055] In the present invention, lithium manganese iron phosphate and a carbon source are mixed by solid phase mixing, without the need for a traditional spray drying process, which is more conducive to energy saving and consumption reduction; and, since the materials are fully contacted and reacted during the solid phase mixing process, the primary particles are compactly agglomerated and dense with few gaps, so the prepared positive electrode material has a high compaction density.

[0056] Preferably, the carbon source includes any one of glucose, sucrose, starch, acetylene black, porous carbon, polyvinyl alcohol, and graphite, or a combination of at least two of them.

[0057] Preferably, the added amount of the carbon source is 2% to 8% of the mass of the lithium manganese iron phosphate precursor, for example 2%, 3%, 4%, 5%, 6%, 7% or 8%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the sintering temperature is 400-600°C, such as 400°C, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0059] In the present invention, by adjusting the sintering temperature, it is more conducive to obtaining a product with a smaller particle size and uniform surface coating. If the temperature is too high, the size of the primary particles generated will be larger, which is not conducive to the performance of the material rate performance; if the temperature is too low, the carbon source will not be fully carbonized, and the coating on the surface of the positive electrode material will be uneven, resulting in a higher resistivity of the positive electrode material powder, which is not conducive to the performance of the capacity. In addition, sintering at 400-600°C is more conducive to energy saving and consumption reduction compared to the sintering temperature of traditional lithium manganese iron phosphate and carbon source.

[0060] Preferably, the sintering time is ≥ 2 h, for example 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] Preferably, the sintering is performed under the protection of an inert atmosphere.

[0062] Preferably, after the sintering is completed, the steps of crushing, screening and packaging are also included.

[0063] As a preferred technical solution, the preparation method comprises the following steps:

[0064] Adding acid in an amount of 1.0 to 1.5 times the theoretical mass of lithium iron phosphate for acid hydrolysis to the ferrophosphorus slag, adjusting the liquid-solid ratio to (2 to 5):1, and performing acid leaching at 50 to 90° C. for 1 to 5 hours to obtain a leachate and a leach residue;

[0065] Adding manganese salt and iron salt to the leachate to supplement manganese and iron, then mixing with the precipitant solution and the complexing agent solution, controlling the pH of the system to be 3.5 to 7, and performing a coprecipitation reaction at 30 to 90° C. for 1 to 5 hours to obtain a manganese iron phosphate precursor, which is then washed and dried in sequence;

[0066] A lithium hydroxide solution with a concentration of 0.5 to 1.3 mol / L is prepared, and the prepared lithium hydroxide solution is added to the obtained ferromanganese phosphate precursor in a molar ratio of 1:(2 to 3) of the sum of the total molar amounts of manganese and iron in the ferromanganese phosphate precursor to the lithium in the lithium hydroxide, and a hydrothermal reaction is carried out at 150 to 250° C. for more than 2 hours under reaction conditions of a stirring rate of 100 to 250 r / min and a reaction pressure of 1.2 to 1.8 MPa to obtain a lithium ferromanganese phosphate precursor;

[0067] Adding a carbon source to the obtained lithium iron manganese phosphate precursor according to 2% to 8% of the mass of the lithium iron manganese phosphate precursor, mixing them evenly in a solid phase mixing manner, and then sintering them at 400 to 600° C. for more than 2 hours under the protection of an inert atmosphere, and obtaining the battery-grade lithium iron manganese phosphate after crushing, screening and packaging;

[0068] Wherein, the acid used in the acid leaching process includes phosphoric acid.

[0069] In a second aspect, the present invention further provides a battery-grade lithium iron manganese phosphate material, which is prepared by the method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag as described in the first aspect.

[0070] In the present invention, the particle size of the battery-grade lithium manganese iron phosphate material is relatively small, about 50 to 160 nm, and the particle size distribution is uniform, for example, 50 nm, 70 nm, 90 nm, 120 nm, 140 nm or 160 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In a third aspect, the present invention further provides a positive electrode sheet for a lithium-ion battery, wherein the positive electrode sheet comprises the battery-grade lithium iron manganese phosphate material as described in the second aspect.

[0072] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0073] Compared with the prior art, the present invention has the following beneficial effects:

[0074] The preparation method provided by the present invention directly prepares lithium iron manganese phosphate positive electrode material from lithium iron phosphate waste residue. Compared with the traditional process of preparing iron phosphate material only from lithium iron phosphate waste residue, it avoids the additional manganese element doping, lithium matching and sintering process of the iron phosphate material, thereby simplifying the process flow, making the recycling of the entire waste lithium iron phosphate battery more efficient and valuable, and suitable for large-scale production. The preparation process of the present invention can make the recovery rate of phosphorus and iron in the waste residue reach more than 96%, and the obtained lithium iron manganese phosphate material has high purity, small particle size of about 50 to 160nm, and uniform distribution, and the electrical performance can reach the level of battery-grade lithium iron manganese phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is the SEM image of the lithium manganese iron phosphate provided in Example 1.

[0076] Figure 2 This is the SEM image of lithium manganese iron phosphate provided for Comparative Example 3. DETAILED DESCRIPTION

[0077] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0078] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0079] The main components of the phosphoric acid slag used in the following examples and comparative examples are shown in Table 1.

[0080] Table 1

[0081] Fe(%) P(%) Li(%) Ca(%) Mg(%) Si(%) Cu(%) Al(%) C(%) 29.50 16.10 0.25 0.16 0.013 0.01 3.71 1.22 10.10

[0082] The phosphoric acid slag used in the present invention is prepared by the following method:

[0083] The waste lithium iron phosphate batteries are disassembled after discharge to obtain positive electrode powder, phosphoric acid solution and hydrogen peroxide are added, and after the iron phosphate and lithium are separated, solid-liquid separation is performed by suction filtration, wherein the liquid is lithium solution and the solid is phosphorus iron slag.

[0084] Example 1

[0085] This embodiment provides a method for preparing battery-grade lithium iron manganese phosphate by extracting lithium iron phosphate slag, and the preparation method is as follows:

[0086] Phosphoric acid in an amount of 1.3 times the theoretical mass of lithium iron phosphate for acid hydrolysis is added to the ferrophosphorus slag, the liquid-solid ratio is adjusted to 3:1, and acid leaching is performed at 70° C. for 3 h to obtain a leachate and a leach residue;

[0087] Manganese sulfate and ferric sulfate are added to the leaching solution to supplement manganese and iron, and then mixed with sodium hydroxide solution and ammonia water, the pH of the system is controlled to be 5, and a coprecipitation reaction is carried out at 60° C. for 3 hours to obtain a manganese iron phosphate precursor, which is then washed and dried in sequence;

[0088] A lithium hydroxide solution with a concentration of 0.9 mol / L is prepared, and the prepared lithium hydroxide solution is added to the obtained ferromanganese phosphate precursor according to a molar ratio of the sum of the total molar amounts of manganese and iron in the ferromanganese phosphate precursor to the lithium in the lithium hydroxide of 1:2.5, and a hydrothermal reaction is carried out at 200° C. for 3 h under the reaction conditions of a stirring rate of 160 r / min and a reaction pressure of 1.5 MPa to obtain a lithium ferromanganese phosphate precursor;

[0089] Graphite is added to the obtained lithium iron manganese phosphate precursor according to 5% of the mass of the lithium iron manganese phosphate precursor, mixed evenly in a solid phase mixing manner, and then sintered at 500° C. for 3 hours under the protection of an argon atmosphere. After crushing, screening and packaging, the battery-grade lithium iron manganese phosphate is obtained.

[0090] Example 2

[0091] This embodiment provides a method for preparing battery-grade lithium iron manganese phosphate by extracting lithium iron phosphate slag, and the preparation method is as follows:

[0092] Phosphoric acid having the same mass as the theoretical mass of acid-hydrolyzed lithium iron phosphate was added to the ferrophosphorus slag, the liquid-solid ratio was adjusted to 2:1, and acid leaching was performed at 50° C. for 1 hour to obtain a leachate and a leach residue;

[0093] Manganese nitrate and ferric nitrate are added to the leaching solution to supplement manganese and iron, and then mixed with potassium hydroxide solution and citric acid solution, the pH of the system is controlled to be 3.5, and a coprecipitation reaction is carried out at 30° C. for 1 hour to obtain a manganese iron phosphate precursor, which is then washed and dried in sequence;

[0094] A lithium hydroxide solution with a concentration of 0.5 mol / L is prepared, and the prepared lithium hydroxide solution is added to the obtained ferromanganese phosphate precursor in a molar ratio of 1:2 between the sum of the total molar amounts of manganese and iron in the ferromanganese phosphate precursor and the lithium in the lithium hydroxide, and a hydrothermal reaction is carried out at 150° C. for 2 h under reaction conditions of a stirring rate of 100 r / min and a reaction pressure of 1.2 MPa to obtain a lithium ferromanganese phosphate precursor;

[0095] Porous carbon is added to the obtained lithium manganese iron phosphate precursor according to 2% of the mass of the lithium manganese iron phosphate precursor, mixed evenly in a solid phase mixing manner, and then sintered at 400° C. for 2 hours under the protection of an argon atmosphere. After crushing, screening and packaging, the battery-grade lithium manganese iron phosphate is obtained.

[0096] Example 3

[0097] This embodiment provides a method for preparing battery-grade lithium iron manganese phosphate by extracting lithium iron phosphate slag, and the preparation method is as follows:

[0098] Phosphoric acid in an amount of 1.5 times the theoretical mass of lithium iron phosphate for acid hydrolysis is added to the ferrophosphorus slag, the liquid-solid ratio is adjusted to 5:1, and acid leaching is performed at 90° C. for 5 hours to obtain a leachate and a leach residue;

[0099] Manganese chloride and ferric chloride are added to the leaching solution to supplement manganese and iron, and then mixed with ammonium carbonate solution and oxalic acid solution, the pH of the system is controlled to 7, and a coprecipitation reaction is carried out at 90° C. for 5 hours to obtain a manganese iron phosphate precursor, which is then washed and dried in sequence;

[0100] A lithium hydroxide solution with a concentration of 1.3 mol / L is prepared, and the prepared lithium hydroxide solution is added to the obtained ferromanganese phosphate precursor according to a molar ratio of the sum of the total molar amounts of manganese and iron in the ferromanganese phosphate precursor to the lithium in the lithium hydroxide of 1:3, and a hydrothermal reaction is carried out at 250° C. for 4 hours under the reaction conditions of a stirring rate of 250 r / min and a reaction pressure of 1.8 MPa to obtain a lithium ferromanganese phosphate precursor;

[0101] Sucrose is added to the obtained lithium iron manganese phosphate precursor according to 8% of the mass of the lithium iron manganese phosphate precursor, mixed evenly in a solid phase mixing manner, and then sintered at 600° C. for 4 hours under the protection of a helium atmosphere. After crushing, screening and packaging, the battery-grade lithium iron manganese phosphate is obtained.

[0102] Example 4

[0103] The difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added in this embodiment is 1.6 times the theoretical mass of acid-hydrolyzed lithium iron phosphate.

[0104] The rest of the preparation methods and parameters were the same as those in Example 1.

[0105] Example 5

[0106] The difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added in this embodiment is 0.8 times the theoretical mass of acid-hydrolyzed lithium iron phosphate.

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] Example 6

[0109] The difference between this embodiment and embodiment 1 is that the pH of the coprecipitation reaction in this embodiment is 3.2.

[0110] The rest of the preparation methods and parameters were the same as those in Example 1.

[0111] Example 7

[0112] The difference between this embodiment and embodiment 1 is that the pH of the coprecipitation reaction in this embodiment is 8.

[0113] The rest of the preparation methods and parameters were the same as those in Example 1.

[0114] Example 8

[0115] The difference between this embodiment and embodiment 1 is that the reaction temperature of the coprecipitation reaction in this embodiment is 25° C. The other preparation methods and parameters are consistent with those in embodiment 1.

[0116] Example 9

[0117] The difference between this embodiment and embodiment 1 is that the reaction temperature of the coprecipitation reaction in this embodiment is 130° C. The other preparation methods and parameters are consistent with those in embodiment 1.

[0118] Example 10

[0119] The difference between this embodiment and embodiment 1 is that the reaction time of the coprecipitation reaction in this embodiment is 0.5 h. The other preparation methods and parameters are the same as those in embodiment 1.

[0120] Embodiment 11

[0121] The difference between this embodiment and embodiment 1 is that the reaction time of the coprecipitation reaction in this embodiment is 8 hours. The other preparation methods and parameters are the same as those in embodiment 1.

[0122] Example 12

[0123] The difference between this embodiment and embodiment 1 is that the reaction temperature of the hydrothermal reaction in this embodiment is 100° C. The other preparation methods and parameters are consistent with those in embodiment 1.

[0124] Embodiment 13

[0125] The difference between this embodiment and embodiment 1 is that the reaction temperature of the hydrothermal reaction in this embodiment is 300° C. The other preparation methods and parameters are consistent with those in embodiment 1.

[0126] Embodiment 14

[0127] The difference between this embodiment and embodiment 1 is that this embodiment adopts traditional liquid phase mixing and adds a spray drying process. The liquid phase mixing method is as follows:

[0128] Add lithium manganese iron phosphate precursor, graphite and magnesium oxide into a ball mill, grind large particles to D50 = 10-30 μm, then sand grind to D50 < 2 μm, mix thoroughly, and then spray dry the resulting slurry, the spray material D50 = 10-40 μm.

[0129] The rest of the preparation methods and parameters were the same as those in Example 1.

[0130] Embodiment 15

[0131] The difference between this embodiment and embodiment 1 is that the sintering temperature in this embodiment is 800°C.

[0132] The rest of the preparation methods and parameters were the same as those in Example 1.

[0133] Comparative Example 1

[0134] The difference between this comparative example and Example 1 is that the acid used in the acid leaching process of this comparative example is sulfuric acid.

[0135] The rest of the preparation methods and parameters were the same as those in Example 1.

[0136] Comparative Example 2

[0137] The difference between this comparative example and Example 1 is that the acid used in the acid leaching process of this comparative example is hydrochloric acid.

[0138] The rest of the preparation methods and parameters were the same as those in Example 1.

[0139] Comparative Example 3

[0140] This comparative example provides a method for preparing lithium iron manganese phosphate by extracting lithium iron phosphate slag, and the preparation method is as follows:

[0141] Phosphoric acid in an amount of 1.3 times the theoretical mass of lithium iron phosphate for acid hydrolysis is added to the ferrophosphorus slag, the liquid-solid ratio is adjusted to 3:1, and acid leaching is performed at 70° C. for 3 h to obtain a leachate and a leach residue;

[0142] A lithium hydroxide solution with a concentration of 0.9 mol / L is prepared, and the prepared lithium hydroxide solution and its manganese sulfate and iron sulfate are added to the leachate according to a molar ratio of the sum of the total molar amounts of manganese and iron elements to the lithium element of 2.5:1, and a hydrothermal reaction is carried out at 200° C. for 3 h under the reaction conditions of a stirring rate of 160 r / min and a reaction pressure of 1.5 MPa to obtain a lithium iron manganese phosphate precursor;

[0143] Graphite is added to the obtained lithium iron manganese phosphate precursor according to 5% of the mass of the lithium iron manganese phosphate precursor, mixed evenly in a solid phase mixing manner, and then sintered at 500° C. for 3 hours under the protection of an argon atmosphere. After crushing, screening and packaging, the lithium iron manganese phosphate is obtained.

[0144] Performance Testing

[0145] The lithium manganese iron phosphate prepared in Example 1 and Comparative Example 3 was subjected to SEM test. The test results are as follows: Figure 1 and Figure 2 shown.

[0146] Figure 1 The SEM image of lithium manganese iron phosphate provided in Example 1 is shown. Figure 2 The SEM image of lithium manganese iron phosphate provided in Comparative Example 3 is shown. Figure 1 and Figure 2It can be seen from the comparison that the method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag provided by the present invention can prepare nano-scale lithium iron manganese phosphate products, and the lithium iron manganese phosphate particle size is 50-160nm, and the particle size distribution is uniform; without co-precipitation reaction, only one-step solvent thermal reaction is carried out to prepare the lithium iron manganese phosphate material, then obvious agglomeration phenomenon occurs, the particle size is between 100 and 500nm, and the product particle size is large and unevenly distributed.

[0147] The lithium manganese iron phosphate prepared in Examples 1 to 15 and Comparative Examples 1 to 3 was tested for element recovery rate, product particle size and product purity. The test results are shown in Table 2.

[0148] Table 2

[0149]

[0150]

[0151] The lithium manganese iron phosphate prepared in Examples 1 to 15 and Comparative Examples 1 to 3 was used as the positive electrode material to assemble a lithium ion battery and perform an electrochemical performance test. The specific preparation method and test conditions are as follows:

[0152] Preparation method

[0153] (1) Positive electrode sheet: Lithium iron phosphate, carbon nanotubes, polyvinylidene fluoride and sodium N-methylpyrrolidone were mixed in a mass ratio of 97:1:2:100 to prepare a uniform positive electrode slurry, which was sieved and coated on a positive electrode current collector aluminum foil, dried at 80°C for 1 h, and rolled using a roller at a unit length load of 10×104 N / m to obtain a positive electrode sheet.

[0154] (2) Negative electrode sheet: The negative electrode active material, conductive agent, binder and thickener were mixed in a mass ratio of 96.0:1.0:1.5:1.5, added into deionized water at a solid content of 40 wt%, and stirred to make a uniform negative electrode slurry. After passing through a 100 mesh sieve, the slurry was coated on the negative electrode current collector copper foil, dried, and rolled with a roller at a speed of 10×10 4 The negative electrode sheet was obtained by rolling the sample under a load of 100 N / m per unit length.

[0155] (3) Diaphragm: PE porous polymer film is used as the diaphragm.

[0156] (4) Assembly of lithium-ion batteries: The positive electrode sheet, separator and negative electrode sheet are wound in sequence to obtain a battery cell; the battery cell is packaged with an aluminum-plastic film, baked to remove water, and then injected with electrolyte. After vacuum packaging, storage, formation, secondary sealing and shaping, a lithium-ion battery is obtained.

[0157] Test conditions

[0158] The battery's discharge capacity in grams was tested at a temperature of 25±2°C, a test voltage of 2.5-4.25V, and current densities of 0.1C, 0.33C, 0.5C, and 1C, and the battery's cycle retention rate was tested after 300 cycles at 0.1C.

[0159] The test results are shown in Table 3:

[0160] Table 3

[0161]

[0162]

[0163] From Table 2 and Table 3, we can get:

[0164] It can be seen from Examples 1 to 3 that the method of the present invention is used to prepare lithium iron manganese phosphate positive electrode material from lithium iron phosphate waste residue, so that the recovery rate of phosphorus and iron in the waste residue can reach more than 96%, and the obtained lithium iron manganese phosphate material has high purity, small particle size of about 50 to 160 nm, and uniform distribution, and the electrical performance can reach the level of battery-grade lithium iron manganese phosphate.

[0165] From the comparison between Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that in the present invention, phosphoric acid is selected as the acid solution in the acid leaching process, which can improve the purity of the product; from the comparison between Example 1 and Comparative Example 3, it can be seen that the lithium manganese iron phosphate precursor is prepared step by step by coprecipitation reaction and solvothermal reaction, which can make the product purity higher, the product particle size smaller and the distribution more uniform, thereby improving its electrochemical performance.

[0166] From the comparison of Example 1, Example 4 and Example 5, it can be seen that the amount of phosphoric acid added in the acid leaching process of the present invention affects the recovery rate of phosphorus and iron and the purity of the product lithium manganese iron phosphate. If the amount of phosphoric acid added is too low, part of the phosphorus and iron in the ferrophosphorus slag will not be fully leached, resulting in low recovery rates of phosphorus and iron and low purity of the ferrophosphorus slag.

[0167] From the comparison of Example 1, Example 6 and Example 7, it can be seen that the present invention can further improve the purity of lithium manganese iron phosphate by controlling the pH of the coprecipitation reaction within the range of 3.5 to 7. If the pH value is too high, impurities such as iron hydroxide and manganese oxyhydroxide may appear, resulting in a decrease in product purity and ultimately affecting its electrochemical performance.

[0168] From the comparison of Example 1, Example 8 and Example 9, it can be seen that the present invention can further improve the purity of the product, make the product particle size smaller, and better control the product particle size distribution by controlling the temperature of the coprecipitation reaction within the range of 30 to 90°C, thereby improving its electrochemical performance.

[0169] From the comparison between Example 1, Example 10 and Example 11, it can be seen that the present invention can further improve the purity of the product by controlling the duration of the coprecipitation reaction within the range of 1 to 5 hours, which helps to obtain a product with smaller particle size and more uniform distribution.

[0170] From the comparison of Example 1, Example 12 and Example 13, it can be seen that the reaction temperature of the hydrothermal reaction in the present invention will affect the electrochemical properties of the product lithium manganese iron phosphate. This is because the temperature of the hydrothermal reaction will affect the structure of the product. Too low a temperature is not conducive to crystallization, while too high a temperature will reduce the compaction density of the material.

[0171] From the comparison between Example 1 and Example 14, it can be seen that the mixing method of lithium manganese iron phosphate and the carbon source in the present invention will affect the performance of the product. This is because the materials are fully contacted and reacted during the solid-phase mixing process, and the primary particles are compactly agglomerated and dense with few gaps, so the prepared positive electrode material has a high compaction density.

[0172] From the comparison between Example 1 and Example 15, it can be seen that the sintering temperature in the present invention will affect the particle size of the product. By controlling the sintering temperature within the range of 400-600°C, it is more conducive to obtaining a product with a smaller particle size and uniform surface coating, thereby optimizing its electrochemical performance.

[0173] In summary, the present invention uses phosphoric acid in the acid leaching process, which can avoid the introduction of additional impurity elements compared to the use of sulfuric acid or hydrochloric acid system, so that the purity of the final product is high; by adding manganese salts and iron salts to the leachate to supplement manganese and iron, on the one hand, the ratio of manganese and iron elements in the obtained lithium manganese iron phosphate product can be adjusted, and on the other hand, after the concentration of manganese and iron elements in the leachate increases, the precipitation process of manganese and iron elements will be promoted, thereby improving the purity of the product. In addition, the present invention prepares the lithium manganese iron phosphate precursor step by step through coprecipitation reaction and solvent thermal reaction. On the one hand, first preparing ferromanganese phosphate through coprecipitation reaction can make the product purer. At the same time, hydrothermal reaction with lithium hydroxide on the basis of ferromanganese phosphate can make the filtrate mainly lithium hydroxide, thereby realizing the recycling of lithium hydroxide solution; on the other hand, the coprecipitation reaction and the hydrothermal reaction cooperate to jointly control the particle size of the precursor, so that the product particle size is small and uniform.

[0174] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag, characterized in that: The method comprises: The ferrophosphorus slag is subjected to acid leaching to obtain a leaching solution and a leaching slag; Adding manganese salt and iron salt to the leaching solution to supplement manganese and iron, and then mixing with a precipitant solution and a complexing agent solution to perform a coprecipitation reaction to obtain a manganese iron phosphate precursor; The manganese iron phosphate precursor is subjected to a hydrothermal reaction with a lithium source to obtain a manganese iron phosphate lithium precursor; Sintering the lithium iron manganese phosphate precursor to obtain the battery-grade lithium iron manganese phosphate; Wherein, the acid used in the acid leaching process includes phosphoric acid.

2. The method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag according to claim 1, characterized in that: During the acid leaching process, the liquid-to-solid ratio is (2-5):1; Preferably, the concentration of the phosphoric acid is 60% to 85%; Preferably, the acid leaching temperature is 50-90°C; Preferably, the acid leaching time is 1 to 5 hours; Preferably, the amount of phosphoric acid added is 1.0 to 1.5 times the theoretical mass of acid-hydrolyzed lithium iron phosphate; Preferably, the pH of the leachate is 0.5-1.

2.

3. The method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag according to claim 1 or 2, characterized in that: The pH of the coprecipitation reaction is 3.5 to 7, preferably 3.5 to 5.0; Preferably, the reaction temperature of the coprecipitation reaction is 30 to 90°C; Preferably, the reaction time of the coprecipitation reaction is 1 to 5 hours; Preferably, the product after the coprecipitation reaction is washed and dried in sequence; Preferably, the precipitant comprises any one of sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia water, ammonium carbonate, and ammonium bicarbonate, or a combination of at least two thereof; Preferably, the complexing agent comprises any one of ammonia, citric acid, oxalic acid and a hydroxycarboxylate complexing agent or a combination of at least two thereof.

4. The method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag according to any one of claims 1 to 3, characterized in that: The ratio of the total molar amount of manganese and iron in the ferromanganese phosphate precursor to the molar amount of lithium in the lithium source is 1:(2-3); Preferably, the solution concentration of the lithium source is 0.5 to 1.3 mol / L; Preferably, the molar ratio of the lithium source to ferromanganese phosphate is 2 to 3:1; Preferably, the lithium source comprises lithium hydroxide; Preferably, the reaction temperature of the hydrothermal reaction is 150-250°C; Preferably, the reaction time of the hydrothermal reaction is ≥ 2h; Preferably, the stirring rate of the hydrothermal reaction is 100 to 250 r / min; Preferably, the reaction pressure of the hydrothermal reaction is 1.2-1.8 MPa.

5. The method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag according to any one of claims 1 to 4, characterized in that: The lithium manganese iron phosphate precursor is first mixed with a carbon source and then sintered; Preferably, the mixing comprises solid phase mixing; Preferably, the carbon source comprises any one of glucose, sucrose, starch, acetylene black, porous carbon, polyvinyl alcohol, and graphite, or a combination of at least two thereof; Preferably, the added amount of the carbon source is 2% to 8% of the mass of the lithium iron manganese phosphate precursor.

6. The method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag according to any one of claims 1 to 5, characterized in that: The sintering temperature is 400-600°C; Preferably, the sintering time is ≥ 2h; Preferably, the sintering is carried out under the protection of an inert atmosphere; Preferably, after the sintering is completed, the steps of crushing, screening and packaging are also included.

7. The method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag according to claim 1, characterized in that: The method comprises: Adding acid in an amount of 1.0 to 1.5 times the theoretical mass of lithium iron phosphate for acid hydrolysis to the ferrophosphorus slag, adjusting the liquid-solid ratio to (2 to 5):1, and performing acid leaching at 50 to 90° C. for 1 to 5 hours to obtain a leachate and a leach residue; Adding manganese salt and iron salt to the leachate to supplement manganese and iron, then mixing with the precipitant solution and the complexing agent solution, controlling the pH of the system to be 3.5 to 7, and performing a coprecipitation reaction at 30 to 90° C. for 1 to 5 hours to obtain a manganese iron phosphate precursor, which is then washed and dried in sequence; A lithium hydroxide solution with a concentration of 0.5 to 1.3 mol / L is prepared, and the prepared lithium hydroxide solution is added to the obtained ferromanganese phosphate precursor in a molar ratio of 1:(2 to 3) of the sum of the total molar amounts of manganese and iron in the ferromanganese phosphate precursor to the lithium in the lithium hydroxide, and a hydrothermal reaction is carried out at 150 to 250° C. for more than 2 hours under reaction conditions of a stirring rate of 100 to 250 r / min and a reaction pressure of 1.2 to 1.8 MPa to obtain a lithium ferromanganese phosphate precursor; Adding a carbon source to the obtained lithium iron manganese phosphate precursor according to 2% to 8% of the mass of the lithium iron manganese phosphate precursor, mixing them evenly in a solid phase mixing manner, and then sintering them at 400 to 600° C. for more than 2 hours under the protection of an inert atmosphere, and obtaining the battery-grade lithium iron manganese phosphate after crushing, screening and packaging; Wherein, the acid used in the acid leaching process includes phosphoric acid.

8. A battery-grade lithium iron manganese phosphate material, characterized in that: The battery-grade lithium iron manganese phosphate material is prepared by the method for preparing battery-grade lithium iron manganese phosphate from lithium iron phosphate slag as described in any one of claims 1 to 7.

9. A positive electrode sheet for a lithium ion battery, characterized in that: The positive electrode sheet includes the battery-grade lithium iron manganese phosphate material as described in claim 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Method for wet recycling of waste lithium iron phosphate positive electrode material

    CN116281916A

Cited By

  • Method for preparing ferromanganese phosphate from waste ferrophosphorus slag

    CN120646801A

  • Method for preparing manganese iron phosphate by using waste phosphorus iron slag

    CN120646801B

  • Method for preparing lithium iron manganese phosphate by recycling waste lithium iron phosphate lithium extraction slag

    CN122380327A